2019
DOI: 10.1007/s00216-019-01907-x
|View full text |Cite
|
Sign up to set email alerts
|

Arsenolipids are not uniformly distributed within two brown macroalgal species Saccharina latissima and Alaria esculenta

Abstract: Brown macroalgae Saccharina latissima (30–40 individuals) and Alaria esculenta (15–20 individuals) were collected from natural populations in winter in Iceland. The algal thalli were sectioned into different parts (e.g. holdfast, stipe, old frond, young frond and sori-containing frond sections) that differed in age and biological function. The work elucidated that arsenic (As) was not uniformly distributed within the two brown macroalgal species, with lower levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…The comparison of reports on the concentrations (mg kg -1 ) of total As in Icelandic A . esculenta from the Pétursdóttir and colleagues [ 37 ] and present studies showed for: stipes (53 ± 3 and 45 ± 6); midrib (43 ± 4 and 23 ± 7); and blade (93 ± 4 and 31 ± 16) respectively. With regards to the As content (mg kg -1 ) in Icelandic S .…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The comparison of reports on the concentrations (mg kg -1 ) of total As in Icelandic A . esculenta from the Pétursdóttir and colleagues [ 37 ] and present studies showed for: stipes (53 ± 3 and 45 ± 6); midrib (43 ± 4 and 23 ± 7); and blade (93 ± 4 and 31 ± 16) respectively. With regards to the As content (mg kg -1 ) in Icelandic S .…”
Section: Resultssupporting
confidence: 68%
“…With regards to the As content (mg kg -1 ) in Icelandic S . latissima , the Pétursdóttir and colleagues [ 37 ] and present studies reported for: stipes (53 ± 4 and 75 ± 32); and blade ([117 ± 9–old frond and 116 ± 6–young frond] and 53 ± 7) respectively.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…esculenta from the Pétursdóttir and colleagues [37] and present studies showed for: stipes (53 ± 3 and 45 ± 6); midrib (43 ± 4 and 23 ± 7); and blade (93 ± 4 and 31 ± 16) respectively. With regards to the As content ( mg kg -1 ) in Icelandic S. latissima, the Pétursdóttir and colleagues [37] and present studies reported for: stipes (53 ± 4 and 75 ± 32); and blade ([117 ± 9 -old frond and 116 ± 6 -young frond] and 53 ± 7) respectively.…”
Section: The Comparison Of Reports On the Concentrations ( Mg Kg -1 )supporting
confidence: 66%
“…Several studies have contributed to our understanding of the occurrence of arsenolipids [16][17][18][19][20][21][22], but we still have only limited knowledge about the metabolism of these compounds and their behavior in natural systems. In this regard, two recent studies by Glabonjat et al [19,22] have revealed the likely significance of phytyl 2-O-methyl arsenosugars in the natural cycling of arsenic.…”
Section: Introductionmentioning
confidence: 99%